The Influence of Rewards on Student Learning Outcomes in the Department of Office Automation and Governance at SMK Negeri 4 Takalar - Sirajuddin Saleh; Magfirah Magfirah; Risma Niswaty; Haerul Haerul; Jamaluddin Jamaluddin (Universitas Negeri Makassar, 2022)
Learning outcomes are changes that are obtained by students after going through the learning process in the form of changes in attitudes, knowledge and skills. One of the factors that can affect learning outcomes is the provision of rewards. So, this research aims to find outthe effect of giving rewards on learning outcomesstudents majoring in Office Administration Automation at SMK Negeri 4 Takalar. Therefore, to achieve this goal the researchers used data collection techniques, namely by using questionnaires, interviews and documentation. The number of samples is 51 respondents. The data analysis technique used is descriptive analysis using percentages and for inferential analysis techniques using data normality test, product moment correlation analysis, simple linear regression statistics. The results of the study show that the awarding of students majoring in Office Automation Governance at SMK Negeri 4 Takalar is in the good category, and for the learning outcomes of students majoring in Office Administration Automation at SMK Negeri 4 Takalar are in the high category. based on the results of the product moment correlation test analysis, there is a relationship between these variables. So that it is stated that there is a positive effect of giving rewards on the learning outcomes of students majoring in Office Administration Automation at SMK Negeri 4 Takalar.